The role of social capital in enhancing the welfare of pre-prosperous families - Hasbiah, Sitti; Bado, Basri; Tahir, Thamrin; Hasan, Muhammad (The Economics and Finance Letters, 2024)
This study delves into the intricate relationship between social capital and the economic resilience of pre-prosperous families in South Sulawesi Province, Indonesia, focusing mainly on the elements of trust, reciprocal relationships, and social networks. A quantitative research methodology was employed, and a sample of 217 impoverished families was randomly selected from a total population of 103,015 households spanning nine regencies and cities within the province. Through the application of structural equation modeling, the research demonstrates the substantial impact of social capital on both household expenditure and the overall welfare of impoverished families, highlighting its fundamental role in bolstering economic well-being within these communities. The study’s findings underscore the critical importance of social capital in not only augmenting household spending but also in enhancing the welfare of economically disadvantaged families, with broader implications for combating poverty, reducing socioeconomic disparities, and fostering sustainable economic progress throughout the region. By elucidating the ways in which social capital shapes the microeconomic resilience of families, this research highlights the transformative potential of social capital in driving economic development and improving the quality of life for less affluent households in South Sulawesi Province. Policymakers and practitioners can utilize these insights to develop targeted interventions that empower local residents, foster supportive networks, and ultimately bolster the economic resilience of disadvantaged families, contributing to sustainable development and poverty alleviation efforts.